Pengaruh Pendidikan Ekonomi Keluarga Terhadap Perilaku Produktif Anak Dengan Religius Sebagai Variabel Mediasi - Nabila Fitria; Budiandru Budiandru (Jurnal Pendidikan Ekonomi (JUPE), 2023)
The research aim to examining the effect of family economic education on the productive behavior of children with religion as a mediating variable in adolescents in Lubang Buaya Village. This research is an associative quantitative research in which the research subjects were teenagers from Lubang Buaya Village, totaling Â±120 respondents. Sampling was carried out using non-probability sampling with purposive sampling technique. The data collection method used a questionnaire which was distributed to teenagers in the Lubang Buaya Village. Data analysis technique using mediation regression analysis. The research results obtained include. First, family economic education has a positive and significant effect on the productive behavior of children in Lubang Buaya Village. Second, religion has a positive and significant effect on the productive behavior of children in Lubang Buaya Village. Third, religion strengthens the relationship between family economic education and children's productive behavior in Lubang Buaya Village.